Heating-responsive shape-memory effect in thermoplastic polyurethanes with low melt-flow index - Sun, Li (2015)
The heating-responsive shape-memory effect (SME) based on melting in two thermoplastic polyurethanes (TPUs) with low melt-flow index is experimentally investigated. It is revealed that after severe deformation in either tension or impression at room temperature, upon heating to the melting temperature, significant shape recovery is achieved. The underlying mechanism for the heating-responsive shape recovery (based on melting) in such a type of polymers without crosslinking is proposed. This mechanism is generic and should be applicable to most thermoplastic polymers with a low melt-flow index.